REHABILITATIONPhysical activity in patients with grown-up congenital heart defects after comprehensive cardiac rehabilitation - Gierat-Haponiuk, Katarzyna; Haponiuk, Ireneusz; Jaworski, Radosław; Chojnicki, Maciej; Szalewska, Dominika; Leszczyńska, Katarzyna; Bakuła, Stanisław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction: The group of grown-up patients with congenital heart defects (grown-up congenital heart – GUCH) complains of a number of specific medical and non-medical problems. The presented program of comprehensive cardiac rehabilitation (CCR-GUCH), dedicated to the above mentioned group, can potentially improve the physical activity of GUCH patients. Aim : The aim of the study was to assess the effect of the comprehensive cardiac rehabilitation program on the physical activity of GUCH patients. Material and methods: The invitation to take part in the CCR-GUCH program was addressed to a group of 57 patients (mean age: 23.7 ± 4.1 years) who had undergone the surgical correction of ventricular septal defects (VSD) or atrial septal defects (ASD) at least 12 months earlier. The patients were divided into two groups: A – patients undergoing rehabilitation, and B – patients who did not participate in the program. The patients were initially examined using functional and stress tests, and the program of comprehensive cardiac rehabilitation was started in group A. After 30 days, the patients from both groups underwent further testing using the same methods as during the initial evaluation. Results: After one month of rehabilitation, the physical activity parameters of patients participating in the CCR-GUCH program (group A) were significantly better than those observed among non-participants (group B). Conclusions: The introduction of the comprehensive rehabilitation program improves the physical activity and, consequently, the quality of life of GUCH patients. The CCR-GUCH program appears to be a justified supplement to holistic care in the late rehabilitation of patients after the surgical correction of congenital heart defects.